Relationship between Affective Function and Family Socialization Function with Young Women's Courtship Behavior - Safitri , Nila; Silvanasari , Irwina Angelia; Tursina , Hella Meldy (Journal of Nursing Periodic, 2024)
Courtship in deviant adolescents is characterized by kissing, hugging, and having sexual relations outside marriage. Family closeness and parenting should be able to minimize the occurrence of deviant dating behavior in adolescents. This study aimed to determine the relationship between family affective function and family socialization function in adolescent girls' courtship behavior. This research method is quantitative research with a cross-sectional approach. The population in this study was all grade 7and grade 8 girls of junior high school in Jember, with 226 female students. The sample of this study a mounted to 144 female students. This study used a purposive sampling technique. The independent variable is the affective function of the family and the socialization function of the family; the dependent variable is the courtship behavior of adolescent girls. Data collection in this study used questionnaires on respondent characteristics, family affective function, family socialization function,and dating behavior that had been tested for validity and reliability. The study was analyzed using Fisher's statistical test. The results of this study showed that the affective function of the family functioned as much (95.1%), the family socialization function functioned as much (93.8%), thecourtship behavior of adolescent girls was at risk (58.3%), there was no relationship between the affective function of the family and the dating behavior of young women, and there was no relationship between the function of family socialization and the dating behavior of young women. Young women should have knowledge, attitudes, and behaviors about good reproductive health to avoid risky dating behaviors. Families should maintain optimization of affective function and socialization function in the family and maintain a good friendship environment in young women. Families should also provide early sexuality education to children to prevent risky dating behavior.